Reconciliation through remembrance?: War memorials and the victims of Vukovar - Clark, Janine Natalya (International journal of transitional justice, 2013)
Memorials remain a relatively under-investigated dimension of transitional justice. Seeking to address this gap, this empirical article focuses on the Croatian town of Vukovar to examine whether war memorials can aid postconflict reconciliation, defined as the restoration and repair of relationships and the rebuilding of trust. It argues that Vukovar’s numerous war memorials are obstructing reconciliation between the town’s Croats and Serbs in two main ways. First, they are encouraging selective memory through the erasure of Serb victims. Second, they are contributing to a problem of too much memory, which is preventing society from moving forward.